Temporal dynamics of the Hyalomma marginatum-borne pathogens in southern France - Charlotte Joly-Kukla; Frédéric Stachurski; Maxime Duhayon; Clémence Galon; Sara Moutailler; Thomas Pollet (Current Research in Parasitology and Vector-Borne Diseases)
Spatio-temporal scales have a clear influence on microbial community distribution and diversity and should thus be applied to study the dynamics of microorganisms. The invasive tick species Hyalomma marginatum has recently become established in southern France. It may carry pathogens of medical and veterinary interest including the Crimean-Congo haemorrhagic fever virus, Rickettsia aeschlimannii, Theileria equi and Anaplasma phagocytophilum. Pathogenic communities of H. marginatum have been identified and their spatial distribution characterized, but their temporal dynamics remain unknown. Hyalomma marginatum ticks were collected from hosts at monthly intervals from February to September 2022 in a site in southern France to study their presence and temporal dynamics. Of the 281 ticks analysed, we detected pathogens including R. aeschlimannii, Anaplasma spp. and T. equi with infection rates reaching 47.0%, 4.6% and 11.0%, respectively. A total of 14.6% of ticks were infected with at least Theileria or Anaplasma, with monthly fluctuations ranging from 2.9% to 28.6%. Strong temporal patterns were observed for each pathogen detected, particularly for R. aeschlimannii, whose infection rates increased dramatically at the beginning of summer, correlated with monthly mean temperatures at the site. Based on these results, we hypothesise that R. aeschlimannii may be a secondary symbiont of H. marginatum and could be involved in the stress response to temperature increase and mediate thermal tolerance of H. marginatum. Analysis of monthly and seasonal fluctuations in pathogens transmitted by H. marginatum led us to conclude that the risk of infection is low but persists throughout the period of H. marginatum activity, with a notable increase in summer.